Cloud Computing for Rural Banking (International Journal of Engineering and Computer Science, 2016)
The Rural Banking introduced in villages to give good and better services to the people for the development of their agriculture sector or to help for their small-scale business. The banking sector in India has witnessed a complete transformation both in its functioning and delivery of services to their customers.The banking services in rural areas helps in developing economic factor that changed the profile of the village and the life of its residents. The rural banking plays a major role in the economic development of a country cannot be overlooked. The main goal is based on Cloud computing to help rural banking. Today technology being the main driving force for businesses has made banking customers to sit back at home and run their accounts without walking into the banks for anything and everything. As the advancement of technology has taken place with immense use of internet, mobile phones and online bill payments banking sector in India has a new facet altogether. The cloud computing is one of the developing technology which is being use by all industrial domain in the IT field. In this paper, I proposed the concept of using cloud computing to develop a banking system for rural areas. It considers various factors such as lack of devices and amenities in rural areas and provides efficient functionality to fulfil those gaps. It uses the latest variations of cloud computing technology for filling in the various technological gaps in village areas.The new technologies had made banks to offer new services and products to its customers, which would help improve economic activities.